2000
DOI: 10.1007/pl00000641
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular aspects of Lyme arthritis

Abstract: Lyme disease is a multisystem illness initiated upon infection with the spirochete Borrelia burgdorferi. Whereas the majority of patients who develop Lyme arthritis may be successfully treated with antibiotic therapy, about 10% go on to develop arthritis which persists for months to years, despite antibiotic therapy. Development of what we have termed treatment-resistant Lyme arthritis has previously been associated with both the presence of particular major histocompatibility complex class II alleles and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…arthritis which lasts for more than 1 year in spite of antibiotic treatment [27], the determination of IL-18 may have a prognostic value. It is suggested that this form of LA has an autoimmunological ethiology [35]. Leukocyte functionassociated antigen-1 (LFA-1) was identified as a potential autoantigen in this form of LA [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…arthritis which lasts for more than 1 year in spite of antibiotic treatment [27], the determination of IL-18 may have a prognostic value. It is suggested that this form of LA has an autoimmunological ethiology [35]. Leukocyte functionassociated antigen-1 (LFA-1) was identified as a potential autoantigen in this form of LA [27].…”
Section: Discussionmentioning
confidence: 99%
“…It enables APC to present LFA-1 to immunocompetent cells and initiate the development of arthritis even after the pathogen was eliminated by antibiotic treatment. Immunocompetent cells in response to the interaction with LFA-1 secrete proinflammatory cytokines, which could be responsible for the damage of joints [35]. So the elevated serum level of IL-18 observed in patients with LA could be a predictor of treatment -resistant LA development, especially in patients with HLA DRB1 antigens, and a high ratio of anti-OspA IgG [35,36], but none of patients included in our study developed treatment-resistant LA as evaluated by clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Only a fraction of these cases are being diagnosed and treated, due to an unclear history, equivocal manifestations, inaccurate or insensitive laboratory clinical tests, and underreporting [5]. These undiagnosed and untreated patients may develop chronic infection or late stage Lyme disease such as chronic Lyme arthritis [6,7] and chronic Lyme neuroborreliosis [8,9] which can be devastating in some cases. …”
Section: Introductionmentioning
confidence: 99%
“…There were several factors involved in the lack of sales including the expense, the need for frequent revaccination and widely publicized concerns about a potential relationship with the development of autoimmune arthritis in patients with a specific HLA haplotype (DRB 0401) ref. A region of OspA that spans the amino acid residues 165–173 (OspA 165–173 ) was postulated to be a molecular mimic of human leukocyte function associated antigen - 1 αL326–345 (LFA-1) capable of inducing proliferation of autoreactive T cells [53, 54]. However, since then, multiple lines of evidence have not supported this hypothesis and molecular mimicry of LFA-1 is no longer felt to be a mechanism of antibiotic resistant Lyme arthritis, although other cross-reactions with OspA cannot be ruled out [55].…”
Section: Human Vaccinationmentioning
confidence: 99%